Implications of macroeconomic stabilization policies on financial intermediation - Stephanie Kimani (Kenya Bankers Association (KBA), 2024)
Effective policies to stabilize macroeconomic conditions are essential for economic growth. In the context of this study, policymakers pursue these macroeconomic stability objectives by adjusting fiscal and monetary policy. The study used impulse response functions (IRFs) derived from vector autoregressive (VAR) models to analyze how these policy changes affected credit allocation. Results show that monetary policy changes through CRR and CBR manipulation have a longer lasting impact on private sector credit compared to fiscal policy changes. Due to its direct impact on bank liquidity, CRR changes impact private sector credit more directly compared to variations in CBR. This implies that when macroeconomic stabilization is urgent, adjusting the CRR to influence private sector credit would be more useful. Meanwhile, fiscal policy, as illustrated through total government spending and revenues, tends to impact the quantum of private sector credit instantaneously. However, the impact is short-lived given the evolving nature of the sovereign's wallet. Further, the results show that prudent fiscal consolidation (raising government revenues or reducing government spending or a combination of both) support lending to the private sector.
Keywords: 330; Stabilisierungspolitik; Geldpolitik; Finanzpolitik; Wirkungsanalyse; Kreditgeschäft; Verbraucherkredit; Kenia